PENGARUH PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PERTUMBUHAN EKONOMI, KEMISKINAN, DAN PENGANGGURAN - Hermawan Budi Prasetiyo; Arfi Farida (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2012)
This research measured the regional tax and regional dues toward economic growth, poverty, and unemployment. This purpose is to explain how the impact of regional tax and regional dues to increase economic growth, and to decrease poverty, and unemployment. This is a quantitative research with the basic year model and one lag year model. Using the object from RAPBD on 2006 – 2010 in Bojonegoro district, this research also used ordinary least squares start from best linear unbiased prediction. The result showed that both the model of regional tax and regional dues no influence significantly toward economic growth, poverty, and unemployment. This caused of the regional tax and regional dues not to use for working to increase economic growth, and to decrease poverty, and unemployment.